Current Guidelines for the Management of Patients with Urinary Tract Infection - Alexander A. Baranov; Roman S. Kozlov; Leyla S. Namazova-Baranova; Irina V. Andreeva; Elena A. Vishneva; Nurali Z. Zokirov; Tatiana V. Kulichenko; Tea V. Margieva; Evgeniy V. Dovgan; Olga U. Stetsyuk; Vladimir K. Tatochenko; Olga V. Chumakova; et al. (Педиатрическая фармакология)
Urinary tract infections in children are among the most common bacterial infections in pediatric practice. The article discusses in detail their clinical manifestations, diagnostic criteria, including laboratory and instrumental research methods, as well as treatment strategies, including the choice of antibacterial therapy and the duration of treatment. Special attention is paid to the prevention of recurrence of urinary tract infections. These clinical guidelines are based on the latest scientific research and international standards, which makes them an important tool for pediatricians and other medical professionals involved in the treatment of children with this pathology. The application of these guidelines in practice helps to improve the quality of medical care and reduce the risk of complications associated with urinary tract infections.